E-Comic Science Integrated with PBL Model to Improve Problem Solving Skills - Ahmad Muhlisin; Laili Hidayani; Eko Juliyanto (Jurnal Penelitian Pendidikan IPA, 2023)
Students’ problem-solving skills in natural science are considered low. This research aims to find out the feasibility, effectiveness, and practicality of e-comic media in science learning that are capable of improving problem-solving skills. The research is a research and development with ADDIE development procedures (analysis, design, development, implementation, and Evaluation). The validity level is obtained through expert validation sheets, whereas the effectiveness level is identified through a trial using a one-group pretest-posttest design with a paired sample t-test analysis. Student questionnaires are used to gain the practicality level. The research results indicate that the media expert assessment is 4.43 and the content expert assessment is 4.23 and both are very valid. The effectiveness level generates a t-value of 11.379 with a significance level of 0.05, which means there is a significant improvement in problem-solving skills. The average gain score is 0.56 or in a moderate category. Students’ questionnaires on the e-comic media resulted in a percentage of 83.54%. The research concludes that e-comic media are feasible to be used in improving problem-solving skills in science learning